2018
DOI: 10.1097/acm.0000000000001860
|View full text |Cite
|
Sign up to set email alerts
|

Making the First Cut: An Analysis of Academic Medicine Editors’ Reasons for Not Sending Manuscripts Out for External Peer Review

Abstract: Findings suggest that clear identification of a research question that is addressed by a well-designed study methodology on a topic aligned with the mission of the journal would address many of the problems that lead to rejection through the internal review process. The findings also align with research on external peer review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…A study of internal editor review (before peer review) of manuscripts submitted to Academic Medicine [ 15 ] found the following nine main themes for internal editor rejection (in order of frequency): ineffective study question and/or design, suboptimal data collection process, weak discussion and/or conclusions, unimportant or irrelevant topic to the journal´s mission, weak data analysis and/or presentation of results, text difficult to follow, to understand, inadequate or incomplete introduction, other publishing considerations, and issues with scientific conduct. The main advice for prospective authors was: 1) finding the right fit between the manuscript and the journal, 2) crafting a clear research question and design, and 3) acting responsibly as a researcher.…”
Section: Discussionmentioning
confidence: 99%
“…A study of internal editor review (before peer review) of manuscripts submitted to Academic Medicine [ 15 ] found the following nine main themes for internal editor rejection (in order of frequency): ineffective study question and/or design, suboptimal data collection process, weak discussion and/or conclusions, unimportant or irrelevant topic to the journal´s mission, weak data analysis and/or presentation of results, text difficult to follow, to understand, inadequate or incomplete introduction, other publishing considerations, and issues with scientific conduct. The main advice for prospective authors was: 1) finding the right fit between the manuscript and the journal, 2) crafting a clear research question and design, and 3) acting responsibly as a researcher.…”
Section: Discussionmentioning
confidence: 99%
“…First, if anyone outside of your institution or research team is to benefit from study results, you need to position the study within a broader context and/or a theoretical framework. The importance of theory and transferability to high-quality research has been emphasized repeatedly in our research community [13, 8] but its absence remains one of the main reasons for rejection.…”
Section: Keep Context In Mindmentioning
confidence: 99%
“…Fortunately, there are many publications that offer sound advice to authors, explaining why papers get rejected, [14] and suggesting tips on how to craft powerful manuscripts [5–7]. While this sage counsel can help you write more persuasive manuscripts, there is another community that should advise HPE scholars: journal editors.…”
mentioning
confidence: 99%
“…Of note, not all manuscripts submitted to JMT undergo formal peer review. Abstracts from national meetings, position statements, invited commentaries, and letters to the editor do not require external review; they are evaluated by one of the editors for clarity and formatting alone [9]. Sometimes manuscripts submitted to JMT simply do not fit the journal's scope and mission.…”
mentioning
confidence: 99%